Where there is a will, there is a way: enhancing contraceptive uptake in Pakistan - Mir, Ali; Pearson, Steve; Masood, Irfan (Journal of the Pakistan Medical Association, 2023)
Objectives: To assess the contribution of a series of interventions on contraceptive uptake and reduction in unmet need in areas covered by the Family Advancement for Life and Health project. Method: The study was conducted from 2008-09 to 2011-12 in 14 districts across Pakistan. The sample comprised all urban and rural households in each district. A total of 40 blocks/villages were selected, with 13 households selected per block/village. Within each household, all married women of reproductive age 15-49 years were interviewed, and their husbands who were present at the time were also interviewed to a maximum of 5 per block. Baseline data was collected in 2008-09, while end line data was collected in 2010-11. Change in family planning uptake attributed to the project interventions were estimated. Besides, a situation analysis of service delivery points was also conducted. Data was analysed using SPSS 21. Results: The panel comprised 5,304 women and 950 husbands. Interventions with the most robust effects were LHWs’ home visits, attending women’s group meetings, and watching family planning messages on television (p<0.05). The greatest changes were observed in Khyber Pakhtunkhwa province, in urban areas and among younger women (p<0.05). Conclusion: Investing in public-sector services does pay off in terms of meeting family planning needs, and so do better, wider and clearer communication. Key Words: Contraception, Pakistan, FALAH.